Governance model for South African schools based on a case study at West Bank Secondary School - Van Der Rheede, Christo Owen (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2005.